2019
DOI: 10.1167/19.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Presaccadic motion integration drives a predictive postsaccadic following response

Abstract: Saccadic eye movements sample the visual world and ensure high acuity across the visual field. To compensate for delays in processing, saccades to moving targets require predictions: The eyes must intercept the target's future position to then pursue its direction of motion. Although prediction is crucial to voluntary pursuit, it is unclear whether it is an obligatory feature of saccade planning. Saccade planning involves an involuntary enhanced processing of the target, called presaccadic attention. Does this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(63 citation statements)
references
References 59 publications
5
56
2
Order By: Relevance
“…It is well established that sensory processing among neurons in MT and MST can be strongly influenced by attention (Treue & Maunsell, 1996; Treue & Trujillo, 1999) and also by target selection immediately prior to saccades (Ferrera & Lisberger, 1997; Recanzone & Wurtz, 2000). Recent studies suggest that like target selection in voluntary pursuit, selective attention can modulate ocular following responses (Souto & Kerzel, 2014), and our findings here and previously (Kwon et al, 2019) support this notion. Pre-saccadic attention is thought to operate through feedback from oculomotor planning areas to visual cortex (Moore & Armstrong, 2003; Moore & Fallah, 2004), and while its impact has been studied mainly in visual area V4, it is also thought to occur in MT/MST.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is well established that sensory processing among neurons in MT and MST can be strongly influenced by attention (Treue & Maunsell, 1996; Treue & Trujillo, 1999) and also by target selection immediately prior to saccades (Ferrera & Lisberger, 1997; Recanzone & Wurtz, 2000). Recent studies suggest that like target selection in voluntary pursuit, selective attention can modulate ocular following responses (Souto & Kerzel, 2014), and our findings here and previously (Kwon et al, 2019) support this notion. Pre-saccadic attention is thought to operate through feedback from oculomotor planning areas to visual cortex (Moore & Armstrong, 2003; Moore & Fallah, 2004), and while its impact has been studied mainly in visual area V4, it is also thought to occur in MT/MST.…”
Section: Discussionsupporting
confidence: 90%
“…This reflects a perceptual mis-localization error along the target motion direction that also influences saccade programming by causing saccade end-points to be shifted along the target motion (Kosovicheva et al, 2014). Consistent with previous studies, our earlier study in visually-intact controls found the position of saccade end-points to be displaced along the direction of dot motion contained in a peripheral target aperture (Kwon et al, 2019). Thus, like the PFR, saccade end-points are also influenced by pre-saccadic selection of target motion, providing another measure of the predictive influence of target motion.…”
Section: Supplementary Materialssupporting
confidence: 90%
See 2 more Smart Citations
“… Goettker et al (2019) show that the pursuit and saccadic system share a common internal representation of the target movement and interact closely to improve tracking responses rapidly. Congruently, Kwon et al (2019) show that the integration of position and motion information extends to the ocular following response. Rothwell et al (in press) compared the role of different cues in driving anticipatory smooth pursuit and anticipatory ocular torsion and found that the predictive drive for these two types of eye movements might be partly decoupled.…”
Section: Combining Predictions Of Eye Arm and Object Movementsmentioning
confidence: 99%